B. sin (3x + 4)
C. sin (3x + 4) +3 (x – 1) cos (3x + 4)
D. none of these
So, the area enclosed from x = 1 to x = x (say) is (x – 1) sin (3x + 4)
⇒ A = ∫f(x) dx = F(x) = (x – 1) sin (3x + 4)
⇒ f(x) = F’(x) = sin (3x + 4) + 3(x – 1) cos (3x + 4) (Using u-v rule of differentiation)
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation